Pengaruh Pengembangan Sumber Daya Manusia Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Sosial Kabupaten Bima - Haryanti Haryanti; Kartin Aprianti; Mulyadin Mulyadin (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
According to (Mangkunegara, 2015), performance is the result of work in terms of quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Similarly, (Sedarmayanti, 2011), says that performance is the result of a worker's work through the management process in the organization as a whole. Furthermore, (Fahmi, 2016) states that performance is the results obtained from organizations that have profit-oriented and non-profit-oriented characteristics that are produced within a certain time. To achieve the vision and mission of an organization or agency, the importance of supervising regional administration, as well as the need for human resources who have good performance, it is necessary to improve employee performance by developing human resources because the availability of human resources is the main factor that influences the achievement of professional performance. , to achieve this, organizations or agencies are required to provide quality human resources so that in carrying out their main tasks and functions achieve optimal and useful results, efforts must be made to involve their employees in education and training. According to (Krismiyati, 2017) Human Resource Development is an effort to improve the knowledge, abilities, attitudes of members, organizations, and provide career paths that are supported by organizational flexibility in achieving goals. According to (Budiarti, 2018), human resource development is an effort to improve the technical, theoretical, conceptual and moral abilities of employees in accordance with the needs of the job or position through education and training.